Pathological changes of microcirculatory channel of periodontal tissues, stipulated by increased occlusion load with bruxism and pathological abrasion of solid teeth tissues - Struk, V. (Actual Dentistry, 2018)
Introduction. For bruxism, the formation of pathological abrasion of hard tissues of teeth of various clinical forms and degree of severity with a number of pathological morpho-functional changes of the tooth-jaw system is characteristic. Increased occlusion load, in addition to changes in the anatomical shape of the tooth, causes pathological changes in periodontal tissues, the nature of which remains poorly understood. Purpose. To study changes in the microcirculatory tract of tissues of periodontal teeth due to increased occlusion load in the case of bruxism. Material and methods. We examined 120 patients aged 18 to 65 years with pathological abrasion of hard tissues of teeth of varying degrees, and a control group of patients of the same age period, with physiological forms of Erasure within the enamel, intact dentition and physiological forms of occlusion with the use of clinical methods and laser Doppler flowmetry (LDF). Diagnostics of bruxism was performed by using the BiteStrip device (Germany). Results. In case of preservation of the anatomical shape of the teeth in the primary form of pathological erase complicated by bruxism we determined the increase in the level of the microcirculation of the tissues of the periodontium of the abutment teeth, as a reaction to increased functional load compared with the control. With the loss of anatomic form of the teeth (2/3 of the length from the crown to the gum level) we diagnosed with a significant decrease of the parameters of microcirculation (PM) (e. g., PM the alveolar gum in the 3-rd group was 16.0±0,31 (PM measure) vs. 20±0,16 (PM measure) in persons the 4-th group, respectively), indicating the presence of dystrophic processes and the reduction in reserve capacity of the microvasculature of periodontal tissues due to the lack of optimal functional chewing forces due to violation of the anatomical shape and loss of teeth crowns. Conclusions. Increased occlusal load caused by bruxism and loss of anatomic form of the teeth due to their pathological erasing significantly affects the microcirculation of periodontal tissues, worsen the overall prognosis of orthopedic treatment and requires further study. Key words: pathological abrasion of hard tissues of teeth, occlusion, diagnosis, microcirculation, laser dopplers flowmetry.